Higher prenatal dietary glycemic index in the third trimester of pregnancy is associated with infant negative affect at 6 months - Elizabeth K. Wood; Olivia Nomura; Jennifer C. Ablow; Annaliese Elliot; Angela Horgan; Joel T. Nigg; Hanna C. Gustafsson; Elinor L. Sullivan (Scientific Reports)
Abstract The dietary glycemic index (GI) reflects post-prandial plasma glucose generation rate, with higher-GI foods rapidly increasing blood sugar. Prenatal consumption of high-GI foods is associated with offspring risk for obesity and metabolic disorders. The impact of prenatal dietary GI exposure on infant neurodevelopment remains unclear. Maternal dietary intake, percent adiposity, and insulin resistance were prospectively assessed during the second and third trimesters in a sample of women with healthy, singleton pregnancies (N = 302). Infant negative affect was prospectively assessed at six months using observer ratings (Still Face Paradigm) and caregiver-reports (Infant-Behavior Questionnaire-Revised). Structural equation models assessed the independent effects of second and third trimester maternal dietary GI, adiposity, insulin resistance on infant negative affect, adjusted for relevant covariates. Higher third, but not second, trimester dietary GI was associated with increased observer-rated infant negative affect (β = 0.14, p = .04) and with higher caregiver-reported infant sadness (β = 0.17, p = .01), suggesting a programming effect of prenatal dietary GI on infant neurodevelopment. Targeted interventions that decrease dietary GI in later pregnancy may prove more effective for optimizing infant behavioral health compared to longer-term changes needed to alter metabolic state. Identifying modifiable early contributors to infant negative affect supports proactive strategies for mitigating future psychopathology risk.